Indigenous Identity And The Law: Who Is A Native? - Bulan, Ramy (Journal of Malaysian and Comparative Law, 2019)
Among the many dimensions of a person’s multi-faceted identity, his ethnic identity may have the most profound implications. While ethnic identification generally has to do with people’s feeling and experience of belonging, the recognized label or identity may depend somewhat on who is speaking: the anthropologist or the sociologist, the government official, the visitor or the member of the group himself; for while normatively neutral, ethnic identity may be deployed or defined with a view to achieving certain aims of society. It is in this context that the question of indigenous identity as it stands in Malaysia is important. Within the ambit of indigenous identity, the issue of ’native’ identity is pertinent because of the political and economic implications that flow from it.